Prototyping Video Games with Animation - DAVIS, Richard Christopher (Institutional Knowledge at Singapore Management University, 2011)
This paper outlines a proposed design for PlaySketch, a new video game storyboarding system. PlaySketch borrows ideas from the K-Sketch animation sketching system, which allows short animations to be created in minutes or seconds. We build on K-Sketch in four ways. Key frame animation capabilities, a branching timeline view, microphone and web-cam support, and hooks to connect to online game design documents.